Arsipoda reidi, a new replacement name for Arsipoda montana D’Alessandro, Samuelson & Biondi (Coleoptera: Chrysomelidae) - Biondi, Maurizio; D'Alessandro, Paola (Fragmenta entomologica, 2022)
Arsipoda reidi nom. nov. is proposed for Arsipoda montana D’Alessandro, Samuelson & Biondi, 2016 because the specific name was preoccupied by the species Arsipoda montana Oke, 1932.